Méthode de Violon (1858) de Charles-Auguste de Bériot: perspectivas pedagógicas do fundador da escola franco-belga de violino e suas relações com a pedagogia moderna - Bruna Caroline de Souza (2017)
Founder of Franco-Belgian Violin School, Charles-Auguste de Bériot was responsible for introducing and adapting the brilliant technical style of Niccolò Paganini to the elegance and seriousness of the traditional Parisian style, established from 1782 by G. B. Viotti. This study analyzes one of his most important pedagogical works the Méthode de Violon (1858) in order to promote it as a teaching material of remarkable pedagogical value available to contemporary violin teachers. It includes biographical information about Bériot, discusses his influence on technical and musical developments of the violin from the establishment of the Franco-Belgian Violin School and establishes a dialogue between the content of his Méthode and those present in the treatises of modern pedagogues Leopold Auer (1921), Carl Flesch (2000, 2008) and Ivan Galamian (2013).